2003
DOI: 10.1007/s00705-003-0148-z
|View full text |Cite
|
Sign up to set email alerts
|

Viruses in subgroup 2 of the genus Ilarvirus share both serological relationships and characteristics at the molecular level

Abstract: Sequence data have been determined for 5 members of subgroup 2 of the genus Ilarvirus. These data support the known serological relationships among accepted members of this group and indicate that the ilarvirus Hydrangea mosaic virus (HdMV) is an isolate of Elm mottle virus (EMoV). The close relationships between members of this subgroup, exhibited through the coat proteins coded on RNA 3, extend to the other genomic molecules. Primers designed from the sequences of RNA 1 and RNA 2 of EMoV amplified fragments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…Comparative sequence analysis demonstrates that the 3Ј-terminal AUGC sequence is highly conserved among AMV and ilarvirus RNAs (15), although 3Ј-terminal AAGC (31,32) and AUGA (PubMed nucleotide entry AF434922) have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative sequence analysis demonstrates that the 3Ј-terminal AUGC sequence is highly conserved among AMV and ilarvirus RNAs (15), although 3Ј-terminal AAGC (31,32) and AUGA (PubMed nucleotide entry AF434922) have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Specific reverse transcription-polymerase chain reaction (RT-PCR) tests have been used widely for routine diagnosis of individual Ilarvirus species (Parakh et al, 1994; MacKenzie et al, 1997; Pallás et al, 1998; Scott et al, 2003). However, the infection of some plant hosts by several Ilarvirus species complicates species identification and necessitates the use of several different specific RT-PCR tests for detection.…”
Section: Introductionmentioning
confidence: 99%
“…Ilarviruses have been divided into subgroups based on serological affinities (Fauquet et al , 2005), and the serological relationships have been shown to extend to the molecular properties of some of the viruses within these subgroups (Scott et al , 2003). There are instances in the literature where serological relationships between ilarviruses have not been clear‐cut or are confusing (Scott et al , 2003; Tzanetakis & Martin, 2005), and molecular comparisons have proven to be more reliable in distinguishing viruses than serological data. The phylogenetic trees based on sequence data show clearly that BCRV should be grouped within subgroup 1 of the genus Ilarvirus (Fig.…”
Section: Discussionmentioning
confidence: 99%